2007
DOI: 10.1007/s11085-007-9068-8
|View full text |Cite
|
Sign up to set email alerts
|

Air-Oxidation Behavior of a Cu60Hf25Ti15 Bulk Metallic Glass at 375–520 °C

Abstract: The oxidation behavior of a Cu 60 Hf 25 Ti 15 bulk metallic glass was studied over the temperature range of 375-520°C in dry air. The oxidation kinetics of the amorphous alloy generally followed the parabolic law at all temperatures, with an oxidation rate increasing with temperature. The oxidation rates of the amorphous alloy were much higher than those of polycrystalline pure-Cu, implying that the additions of Hf and Ti accelerated the oxidation reaction. The composition of the scales formed on the amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…It is expected that the cracks formed on the Fe7-BMG provide easy paths for the enhanced inward diffusion of oxygen and outward diffusion of iron, which in turn increase the oxidation rates, as compared to the crystalline alloy. In addition, it is also very likely that the fast oxidation rates of the amorphous alloy with respect to its crystalline counterpart is due to the presence of the excess free volume in the Fe7-BMG, as similar to that reported previously [11]. In other words, the created free volume in the sub-lattice sites of the Fe7-BMG structure may provide a fast diffusion path for cation-and oxygen-diffusion through the substrate, which in turn resulted in an increase of the metal-oxygen reaction, thereby leading to the faster oxidation rates, as compared to its crystalline counterpart.…”
Section: Oxidation Kineticssupporting
confidence: 84%
“…It is expected that the cracks formed on the Fe7-BMG provide easy paths for the enhanced inward diffusion of oxygen and outward diffusion of iron, which in turn increase the oxidation rates, as compared to the crystalline alloy. In addition, it is also very likely that the fast oxidation rates of the amorphous alloy with respect to its crystalline counterpart is due to the presence of the excess free volume in the Fe7-BMG, as similar to that reported previously [11]. In other words, the created free volume in the sub-lattice sites of the Fe7-BMG structure may provide a fast diffusion path for cation-and oxygen-diffusion through the substrate, which in turn resulted in an increase of the metal-oxygen reaction, thereby leading to the faster oxidation rates, as compared to its crystalline counterpart.…”
Section: Oxidation Kineticssupporting
confidence: 84%
“…As also described previously, [11] Cu 2 O has large deviations from the stoichiometry, and its nonstoichiometric value (the x value in Cu 2Àx O) is around 0.002 at 1298 K (1025°C) and 0.1 atm O 2 . On the other hand, Tretyakov et al [12] reported that CuO 1Ày has very small deviations from stoichiometry, and its y value is around 1.1 9 10 À19 at 1073 K (800°C) and 0.21 atm O 2 .…”
Section: Scale Constitution and Phasessupporting
confidence: 73%
“…In addition, the Cu 4 O 3 phase was also observed in a previous study concerning the oxidation of the Cu 60 Hf 25 Ti 15 glassy alloy at 648 K (375°C) to 793 K (520°C). [11] Thus, one may expect that the growth of duplex or complex copper oxides on top of the Pd4-BMG is kinetically favorable. However, the observed results indicated that an exclusive CuO layer was present, which deserves further verification through TEM.…”
Section: Scale Constitution and Phasesmentioning
confidence: 99%
“…The oxidation behaviors have been examined in the Fe, Ni, Zr and Mg based BMGs in Taiwan [75][76][77][78][79][80][81][82]. For the Fe based alloys, the Fe 72 B 22 Y 6 BMG and its crystalline counterpart were studied over the temperature range of 600-700 C in dry air [75].…”
Section: Oxidation and Corrosionmentioning
confidence: 99%
“…The scales formed on the glassy alloy consisted mainly of boron oxide (B 2 responsible for the reduced oxidation rates of the glassy alloy as compared to those of crystalline counterpart. The high-temperature oxidation behaviors of the Zr and Cu based BMGs in dry air or oxygen environment have been systematically examined by Kai and his group [76][77][78][79][80][81][82], including Zr 53 Ni 23.5 Al 23.5 at 400-600 C [76], Cu 60 Hf 25 Ti 15 at 375-520 C [77], Cu 60 Zr 30 Ti 10 and Cu 60 Zr 20 Ti 10 Hf 10 at 350-500 C [78], (Cu 78 Y 22 ) 98 Al 2 amorphous composite at 400-600 C [79] and other systems [80][81][82]. For the Zr 53 Ni 23.5 Al 23.5 system at 400-600 C [76], the oxidation kinetics of the alloy follow the single-or two-stage parabolic rate law at T 500 C, but could be fitted by a three-stage parabolic law at 550-600 C. They found the amounts of Al 2 O 3 and monoclinic-ZrO 2 in the scales increase with the oxidation temperature.…”
Section: Oxidation and Corrosionmentioning
confidence: 99%